Risk Factors for Maternal Body Mass Index and Gestational Weight Gain in Twin Pregnancies - Schubert, Julia; Timmesfeld, Nina; Noever, Kathrin; Behnam, Susann; Vinturache, Angela; Arabin, Birgit (Geburtshilfe und Frauenheilkunde, 2022)
Objective This retrospective cohort study analyzes risk factors for abnormal pre-pregnancy body mass index and abnormal gestational weight gain in twin pregnancies.Methods Data from 10 603/13 682 twin pregnancies were analyzed using uni- and multivariable logistic regression models to determine risk factors for abnormal body mass index and weight gain in pregnancy.Results Multiparity was associated with pre-existing obesity in twin pregnancies (aOR: 3.78, 95% CI: 2.71 – 5.27). Working in academic or leadership positions (aOR: 0.57, 95% CI: 0.45 – 0.72) and advanced maternal age (aOR: 0.96, 95% CI: 0.95 – 0.98) were negatively associated with maternal obesity. Advanced maternal age was associated with a lower risk for maternal underweight (aOR: 0.95, 95% CI: 0.92 – 0.99). Unexpectedly, advanced maternal age (aOR: 0.98, 95% CI: 0.96 – 0.99) and multiparity (aOR: 0.6, 95% CI: 0.41 – 0.88) were also associated with lower risks for high gestational weight gain. Pre-existing maternal underweight (aOR: 1.55, 95% CI: 1.07 – 2.24), overweight (aOR: 1.61, 95% CI: 1.39 – 1.86), obesity (aOR: 3.09, 95% CI: 2.62 – 3.65) and multiparity (aOR: 1.64, 95% CI: 1.23 – 2.18) were all associated with low weight gain. Women working as employees (aOR: 0.85, 95% CI: 0.73 – 0.98) or in academic or leadership positions were less likely to have a low gestational weight gain (aOR: 0.77, 95% CI: 0.64 – 0.93).Conclusion Risk factors for abnormal body mass index and gestational weight gain specified for twin pregnancies are relevant to identify pregnancies with increased risks for poor maternal or neonatal outcome and to improve their counselling. Only then, targeted interventional studies in twin pregnancies which are desperately needed can be performed.
Keywords: gestational weight gain; twin pregnancy; obesity; overweight; underweight